Psychosocial Problems on Defendants in Detention Center - Aisyah Dzil Kamalah; Eka Budiarto (Babali Health, 2022)
Introduction: Psychosocial problems can trouble anyone. Defendants living at a detention center have high risk of experiencing psychosocial problems due to restrictions on social relations with people outside. The purpose of this study was to determine the psychosocial problems experienced by defendants in Pekalongan Detention Center.